'My Memories of the Time We Had Together Are More Important': Direct Cremation and the Privatisation of UK Funerals. (June 2022) - Woodthorpe, Kate; Rumble, Hannah; Corden, Anne; Birrell, John; Schut, Henk; Stroebe, Margaret; Newsom, Cate; Smith, Yvette
Funerals have long been of interest to social scientists. Previous sociological work has examined the relationship between individuality, belief and tradition within funeral services, founded on the assumption that public rituals have psycho-social benefit for organisers and attendees. With the introduction of direct cremation to the UK, and the impact of the COVID-19 pandemic on funeral service attendance in 2020 and 2021, critique of this assumption is now needed. Drawing on interviews with recently bereaved people who organised a direct cremation in late 2017, this article illustrates how compromise, control and consistency are key drivers for not having a funeral service. The article argues that a declining importance in the fate of the body and a move towards 'invite-only' commemorative events represents a waning need for social support offered by a public, communal funeral service. In turn, this indicates a sequestration, or privatisation, of the contemporary funeral.